Criteria to predict carriers of a novel SCN5A mutation in a large Portuguese family affected by the Brugada syndrome - Santos, L. F. (2012)
Brugada syndrome (BrS) is a life-threatening arrhythmia disorder associated with autosomal-dominant mutations in the SCN5A gene. We aimed to characterize the diagnostic challenges and clinical manifestations of a novel SCN5A mutation associated with BrS.